Design of Functional Gradient Porous Structure and its Fabrication using DMLS Process. (2020) - Suresh Babu, A.; Jaivignesh, M.; Srinivasan, S.; Sugavaneswaran, M.
Abstract: The functionally graded material (FGM) is referred as the material which is non-uniform and has changing structure and material composition. FGMs are now being used in different types of areas that are different from the initial area of application. A functional gradient porous structure is designed and modelled as prototype to validate for the mechanical and biomedical applications. In this work, gradient porous structure of Gyroid shape is used to design a model. Gradient porous structure is entirely different from the homogenous porous structure but like homogenous porous structure, it reduces material consumption with maintenance of similar strength. To fabricate the model, stainless steel 316L is used, which is a biomaterial. The effect of functional gradient on the compressive strength of the structures by considering nine different porosities (porosities = 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%) both experimentally and numerically, is studied. The initial stage involved the development of mathematical model of functionally gradient porous structure based on governing equation of Gyroid, which is a triply periodic minimal surface. CAD models of normal porous and gradient porous structures are generated using K3DSurf and Rhinoceros software. Developed structures are manufactured by Direct Metal Laser Sintering (DMLS) Additive manufacturing method with stainless steel 316L as the build material and experimentally tested under quasi static compressive loading conditions. These models are analyzed in ANSYS software. The CAD model is validated by comparing the experimental and numerical results and the Deviation between yield stress from experimental and numerical results obtained was 3.5%.